2022
DOI: 10.1109/access.2022.3230591
|View full text |Cite
|
Sign up to set email alerts
|

ROI-Fuzzy Based Medical Data Authentication Scheme for Smart Healthcare System

Abstract: During the current pandemic, telemedicine applications encourage radiologists to consult patients remotely. Medical images are typically sent over the internet for easy access when diagnosing a patient. Intruders can manipulate these images during communication. Therefore, we require a method of authentication for these images that is capable of authenticating these images before diagnosis. To address these issues, a watermarking scheme has been developed within the scope of this paper. The foundation of antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The findings indicate that the envisaged system exhibited satisfactory performance, even in the presence of a filtering attack. Furthermore, upon conducting a comparative analysis of the outcomes with other extant methodologies, namely [28,[30][31][32], at intensities of 0.05, 0.025, and 0.10 (as presented in Table 5), it was noted that the findings of [31,32] bear similarity to the suggested approach at an intensity of 0.050. At the intensity of 0.025 and 0.010, the performance of our approach is much better than other similar schemes.…”
Section: Jpeg Compressionmentioning
confidence: 98%
See 4 more Smart Citations
“…The findings indicate that the envisaged system exhibited satisfactory performance, even in the presence of a filtering attack. Furthermore, upon conducting a comparative analysis of the outcomes with other extant methodologies, namely [28,[30][31][32], at intensities of 0.05, 0.025, and 0.10 (as presented in Table 5), it was noted that the findings of [31,32] bear similarity to the suggested approach at an intensity of 0.050. At the intensity of 0.025 and 0.010, the performance of our approach is much better than other similar schemes.…”
Section: Jpeg Compressionmentioning
confidence: 98%
“…The obtained results demonstrate that, when exposed to a JPEG compression attack, the proposed approach performed better than expected. Furthermore, upon conducting a comparative analysis of the outcomes with other pre-existing methodologies, namely [28,[30][31][32], concerning quality factors 80 and 90 (as presented in Table 3), it was observed that the outcomes of [28,32] exhibit a resemblance to the proposed scheme at a quality factor of 90. At a quality factor of 80, it can be observed that only the reference [32] is in closer proximity to the subject matter being discussed.…”
Section: Jpeg Compressionmentioning
confidence: 99%
See 3 more Smart Citations